Reproductive performance of cows with subclinical endometritis diagnosed by different cytological thresholds in the postpartum period - Barański, W.; Zduńczyk, S.; Janowski, T. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2013)
Objective: To determine the impact of cytologically determined endometritis (CE) diagnosed according to three different cytological thresholds in the 4th and 6th week postpartum (p. p.) on the subsequent reproductive performance in dairy cows. Material and methods: Dairy cows (n = 222) were clinically examined in the 4th week (Exam I) and in the 6th week (Exam II) p. p. and endometrium samples were collected for cytological examination using the cytobrush method. Three cytological thresholds (percent of polymorphonuclear leucocytes to epithelial cells) were used for categorization of cows: 1) > 18% at Exam I and > 10% at Exam II; 2) > 8% at Exams I and II; 3) > 5% at Exams I and II. The animals were categorized as endometritis positive (CE+) or negative (CE-) according to all cytological thresholds at Exams I and II. For all six experimental groups the following reproductive parameters were calculated: first insemination pregnancy rate, number of services per conception, intercalving period, and total pregnancy rate on day 300 p. p. Results: According to different thresholds prevalence of CE ranged from 48.0% to 65.9% at Exam I and from 26.0% to 34.7% at Exam II. The first insemination pregnancy rate was statistically lower in all CE positive groups at Exam I. Number of inseminations per conception was higher (p < 0.05) in each CE positive cows with exception of group CE+ at Exam II. Intercalving periods were longer in CE cows, and significant (p < 0.05) difference was found for groups ICE+ and ICE- at Exam I. Overall pregnancy rates were similar in cytologically determined endometritis and control cows. Conclusion and clinical relevance: Impaired fertility at herd level may concern only particular reproductive indices. It seems that each herd with subclinical endometritis needs to be evaluated and managed individually, according to the different housing, feeding, and environmental conditions. The first of three thresholds used to cytologically diagnose endometritis seems to be the most reliable when applied in the 4th week p. p.
Keywords: Cytology; endometritis; cow; reproductive parameters